2016
DOI: 10.1026/0049-8637/a000143
|View full text |Cite
|
Sign up to set email alerts
|

Stereotype Threat in der Grundschule

Abstract: Zusammenfassung. Das Ziel der Studie war es zu untersuchen, ob bereits Grundschulkinder von Stereotype-Threat- beziehungsweise Lift-Effekten in ihrer Mathematikleistung beeinflusst werden. Dazu wurde auf eine implizite Manipulation zurückgegriffen, um Geschlechtsstereotype zu aktivieren, bevor ein Mathematiktest absolviert wurde. Bei Mädchen sollte die Aktivierung zu einer schlechteren Leistung führen, während für Jungen ein Leistungsvorsprung erwartet wurde. An der Untersuchung nahmen 120 Viertklässler teil (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…Effects of stereotypes on boys' performance, motivational dispositions, and attitudes toward a domain are less clear, as there are only a few studies on such effects and contradictory findings have been reported. Muzzatti and Agnoli (2007), for example, found no effects of presenting stereotypes on boys' math performance in Grades 3, 5, and 8 as well as their math competence beliefs in Grades 3 and 5 (see also Hermann and Vollmeyer, 2016 for similar results on boys in elementary school). However, among 8th graders, they found higher competence beliefs among boys who were confronted with the stereotype of males' advantage in math compared to the control group (Muzzatti and Agnoli, 2007).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Effects of stereotypes on boys' performance, motivational dispositions, and attitudes toward a domain are less clear, as there are only a few studies on such effects and contradictory findings have been reported. Muzzatti and Agnoli (2007), for example, found no effects of presenting stereotypes on boys' math performance in Grades 3, 5, and 8 as well as their math competence beliefs in Grades 3 and 5 (see also Hermann and Vollmeyer, 2016 for similar results on boys in elementary school). However, among 8th graders, they found higher competence beliefs among boys who were confronted with the stereotype of males' advantage in math compared to the control group (Muzzatti and Agnoli, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…These studies have demonstrated that children in elementary school are already aware of their own gender and show gender-stereotypical views in the domain of math, as they attribute lower math ability and talent to girls and women than to boys and men (e.g., Signorella et al, 1993; Ambady et al, 2001; Passolunghi et al, 2014). In addition, there is research on the short-term effects of stereotypes on math performance among girls of different ages (Ambady et al, 2001; Muzzatti and Agnoli, 2007; Neuville and Croizet, 2007; Tomasetto et al, 2011; Hermann and Vollmeyer, 2016). A meta-analysis by Flore and Wicherts (2015), for instance, found that girls who are reminded of typical gender stereotypes in math exhibit slightly lower math performance compared to girls who are not reminded of such stereotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding other student characteristics, for example, gender, findings have been less consistent. While some studies reported on mathematics teachers having higher expectations for their male students than for their female students (Hermann & Vollmeyer, 2016; Lazarides & Watt, 2015; Lorenz et al., 2016; Ready & Wright, 2011), some studies made opposite findings: teachers formed higher expectations for their female students (e.g. Hinnant et al., 2009; Timmermans et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We formulated the following hypotheses based on our current knowledge. First, we assume the existence of a positive relation between teacher expectations and student SES, as well as higher teacher expectations for male students (H1) (Gentrup et al., 2018; Hermann & Vollmeyer, 2016). Second, we posit that low‐achieving students benefit more from high expectations in mathematics than high‐achieving students (H2a) (Madon et al., 1997).…”
Section: Introductionmentioning
confidence: 99%
“…B. Hermann & Vollmeyer, 2016;Tomasetto, Alparone & Cadinu, 2011). Hinsichtlich (negativer) Einstellungen zu verschiedenen Ethnien wiesen Studien im nicht deutschsprachigen Raum darauf hin, dass auch bereits Kinder zum Beispiel über negative verhaltensbezogene Einstellungen gegenüber Fremdgruppen verfügen können (z.…”
unclassified